Electrochemical characteristics of porous TiO2 encapsulated silicon anode - Jeon, Bup Ju; Lee, Joong Kee (PERGAMON-ELSEVIER SCIENCE LTD, 2011)
TiO2 coated silicon, which was prepared by the modified sol-gel method, was employed as the anode material for lithium secondary batteries and the relationship between the diffusivity and electrochemical characteristics was investigated. The results showed that the physical properties of the samples, such as their diffusivity and pore size distribution, enhanced the cycling efficiency of the TiO2 coated silicon, probably due to the reduction of the side reactions, which may be closely related to the pore size distribution of the TiO2 coating layer. The pore size of the coating layer plays an important role in retarding the lithium ion diffusion. In the experimental range studied herein, higher capacity retention was exhibited for the TiO2 coated silicon prepared at pH 10.7. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: STRUCTURAL EVOLUTION; SECONDARY BATTERIES; THIN-FILMS; ELECTRODE; PERFORMANCE; DEPOSITION; LI